The Influence Of Emotional Intelligence, Adversity Quotient, And Social Intelligence On Students’ Work Readiness - Sani, Maya Arma; Nasution, Nasution (Universitas Muhammadiyah Pontianak, 2025)
This study examines the influence of Emotional Intelligence (EI), Adversity Quotient (AQ), and Social Intelligence (SI) on the job readiness of final-year students at the University of Bengkulu. Using a quantitative approach with purposive sampling, 357 students were analyzed through SPSS 20. The results show that EI, AQ, and SI have a positive and significant impact on job readiness. EI enhances emotional regulation, AQ builds resilience, and SI supports effective interpersonal skills. The study suggests the university strengthen soft skills programs focusing on EI, AQ, and SI to better prepare students for the workforce.